Association of Self-Reported Trouble Hearing and Patient–Provider Communication with Hospitalizations among Medicare Beneficiaries - Reed, Nicholas S. (Semin Hear, 2021)
Several studies have recently illuminated the relationship between hearing loss and hospitalizations, but little is understood as to why hearing loss is associated with greater risk for hospitalizations. This study examines the role of patient–provider communication as the mechanism by which those with hearing loss are more likely to be hospitalized, using the self-reported data from 12,654 Medicare beneficiaries from the 2016 Medicare Current Beneficiary Survey (MCBS) Cost and Use File. Multivariable logistic regression was used to model the odds of any hospitalization in the past year and negative binomial regression to model the incident rate ratio of hospitalization based on number of hospitalizations in the past year. It was found that Medicare beneficiaries who experience impaired communication with their physician due to trouble hearing have greater odds of hospitalization and a higher rate of all hospitalization over a 1-year period. Understanding the complex relationship between hearing loss, patient–provider communication, and hospitalizations may provide health care professionals with a better rational to address not only hearing loss but also impaired communication in the care of an individual.